Pengaruh Pembelajaran Daring Terhadap Hasil Belajar Siswa dengan Berbantu Media Macromedia Flash 8 pada Pembelajaran Matematika Materi Fungsi Komposisi dan Invers - Khusnul Khotimah; Ratih Handayani; Nuri Larasanti (Eksponen, 2022)
Teachers use media, like books and papers, to help students learn. Interactive media, like computers and games, can be more effective in helping students understand the material they are learning. However, at SMA Negeri 1 Abung Semuli, mathematics learning is not using technology to its fullest potential. This is because the teaching materials are not interactive, and the students have difficulty understanding the material. Schools still use media in the form of materials in PDF (Portable Document Format) format. Macromedia Flash 8 is an application for designing interactive and innovative learning materials. Research on the use of macromedia flash 8 in learning mathematics aims to determine whether there is an influence from the media on learning mathematics conducted online on learning outcomes. This research is a qualitative descriptive study using a quasi-experimental design method and the population is all students at SMA Negeri 1 Abung Semuli class X for the 2020/2021 academic year. The sample as an experimental class is class X IPS 1 students and the control class sample is Class X IPS 3. The research data is in the form of tests using multiple choice tests. The test results were analyzed using the t-test with a significant level of (Î±) = 0.05 and tcount = 2.729 and t_table = 2.016, because tcount>ttable which resulted in H0 being rejected. So that the conclusion of the results of this study is that there is an influence of online learning on student learning outcomes assisted by Macromedia Flash 8 media on mathematics learning material composition and inverse functions at SMA Negeri 1 Abung Semuli for the 2020/2020 academic year